A time-geographic approach to identifying daily habitat use patterns for Amazonian Black Skimmers. (May 2020) - Loraamm, R.W.; Goodenough, K.S.; Burch, C.; Davenport, L.C.; Haugaasen, T.
Abstract: Analysis of movement patterns at fine temporal scales may suggest how animals interact with their surrounding habitat. This is particularly useful in determining not only where animals may spend their time, but when and how likely they may be to interact with or utilize specific habitat resources. While previous studies demonstrate various methods seeking to address this concern, most apply for a single individual or a single point pair in a trajectory. However, for practical conservation concerns, information on animal-habitat interactions should be considered at the group level. This paper applies two approaches from movement analysis, the probabilistic voxel-based space-time prism and the comprehensive probability surface, to construct utilization distributions corresponding to specific intervals in time. Utilization distributions are processed towards summary quantification of diel habitat interaction probabilities for multiple individuals. We evaluate this approach using primary tracking data collected from Black skimmers ( Rynchops niger cinerascens ) traversing Manu National Park, Peru and surrounding areas. Habitat interaction graphs were constructed summarizing animal interaction by habitat type and time of day for all individuals tracked. This information was used to corroborate known black skimmer habitat use behaviors. Habitat interaction results were generally consistent with skimmers' known foraging patterns for dawn, dusk and overnight hours. Results also raised a noteworthy use pattern for urban areas at dusk and early evening otherwise unobserved. Findings suggest applicability of this approach for cryptic species where direct observation is difficult, but trajectory data are available. Utility of this method for the practical work of conservationists and related researchers is discussed. Highlights: A time-geographic approach was applied to satellite tracking data for Black Skimmers in the western Amazon Basin. Habitat availability and utilization were explored using a time-geographic framework. Results assist conservation practitioners in scheduling time and location for observation efforts. Results suggest space use patterns for animals from trajectory data and remotely sensed landcover.